2021
DOI: 10.34067/kid.0005082021
|View full text |Cite
|
Sign up to set email alerts
|

A Blueprint for an Integrated Point-of-Care Ultrasound Curriculum for Nephrology Trainees

Abstract: Point-of-care ultrasonography (POCUS) is a limited ultrasound study performed by the clinician at bedside as a component or an adjunct to physical examination. POCUS has multiple applications in nephrology practice including evaluation of obstructive uropathy, objective assessment of volume status, arteriovenous access assessment, and procedural guidance. However, unlike specialties such as emergency medicine, POCUS training is not yet integrated into most nephrology fellowship curricula, and the sonographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 29 publications
(32 reference statements)
0
20
0
Order By: Relevance
“…Similar observations have been replicated in various clinical settings associated with volume derangements, including heart failure, critical illness, and hemodialysis 41–43 . Over the past several years, POCUS has evolved as an enhancement to physical examination in various specialties, including nephrology and critical care 44,45 . It refers to clinician‐performed limited ultrasound examination intended to answer focused clinical questions.…”
Section: Special Considerationsmentioning
confidence: 78%
See 1 more Smart Citation
“…Similar observations have been replicated in various clinical settings associated with volume derangements, including heart failure, critical illness, and hemodialysis 41–43 . Over the past several years, POCUS has evolved as an enhancement to physical examination in various specialties, including nephrology and critical care 44,45 . It refers to clinician‐performed limited ultrasound examination intended to answer focused clinical questions.…”
Section: Special Considerationsmentioning
confidence: 78%
“…[41][42][43] Over the past several years, POCUS has evolved as an enhancement to physical examination in various specialties, including nephrology and critical care. 44,45 It refers to clinician-performed limited ultrasound examination intended to answer focused clinical questions. Bedside sonographic evaluation of the pump (heart), pipes (inferior vena cava, abdominal venous Doppler), and the leaks (extravascular lung water, ascites) facilitates objective assessment of fluid status in conjunction with clinical and laboratory data.…”
Section: Role Of Pocus In Hyponatremiamentioning
confidence: 99%
“…There is a clear interest in this training because several US curricula have been outlined across the stages of medical training. 4,6,77,78 New technologies may also offer unforeseen opportunities. Chen et al 79 demonstrated the use of superresolution ultrasound imaging in the detection of alterations in the renal microvasculature in a murine model of acute kidney injury.…”
Section: Challenges and Opportunities In Kidney Usmentioning
confidence: 99%
“…1,2 Several studies have argued for the formal incorporation of sonography into training and clinical practice, citing its increasing utility and accessibility in nephrology. [3][4][5][6][7] Taken together, advances in beamforming, image acquisition, and image processing make portable US a reality while lowering costs by several orders of magnitude. One of these advances is point-of-care US.…”
mentioning
confidence: 99%
“…POCUS in nephrology is no longer confined to kidney ultrasound or procedural guidance but encompasses a wide range of applications, including lung ultrasound and limited echocardiography for fluid status assessment. 1 , 2 When evaluating a patient with acute kidney injury (AKI), it is important to systematically rule out the potential causes by careful history taking, physical examination, and analysis of laboratory data. POCUS is an adjunct to physical examination and aids in the diagnosis and management of AKI from excluding hydronephrosis to providing real-time insights into hemodynamic status.…”
Section: Introductionmentioning
confidence: 99%